Conceito e classificação da dormência em sementes - Cardoso, Victor José Mendes [UNESP] (2009)
Despite being known to science for quite a long time, the phenomenon of seed dormancy still baffles the scientific community for the multiple complex underlying mechanisms. The current classification systems of seed dormancy attempt to condense all that is known about the phenomenon in an attempt to generate a conceptual database that would enable facilitated interpretation of upcoming information and allow for a better contextuation of research in this field. The present paper is a preliminary overview of the current panorama of concepts and classification systems of seed dormancy that intends to serve as a standpoint for future research in this field.